Resilience of Families of Different Religions in Indonesia between Social and Religious Problems - Setiyanto, Danu Aris (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2022)
Families of different religions are a social fact in plural social life. However, interfaith marriage has always been a controversy and is considered to cause several problems, especially legal, social, and religious debates. Interestingly, some families of different religions can have good family resilience in their conditions facing social problems and religious debates. This article will answer academic anxiety about strengthening family resilience after marriage. We answer this problem with case studies and use a sociological approach. The purpose of this article is used to explain that interfaith families have specific strategies for maintaining the resilience of their families. So, the contribution of theories and experiences of families of different religions needs to be studied in more detail through this article and subsequent research. This article produces an answer that strengthening the resilience of families of couples of different religions is carried out by mutual agreement on childcare, sharing experiences for prospective families of different religions, consultations, and couple communication that does not lead to theological differences.